Biofoam Cassava Starch and Sugarcane Bagasse Cellulose with the Addition of Polyvinyl Alcohol and Chitosan - Nurul Laila Syarifah; Rully Masriatini; Agus Wahyudi; Muhrinsyah Fatimura (CHEESA: Chemical Engineering Research Articles, 2025)
The persistence of non-biodegradable styrofoam waste is contributing to the development of sustainable packaging materials from renewable resources, such as biofoam from natural biopolymers. Therefore, this study aimed to develop biofoam based on cassava starch and cellulose isolated from sugarcane bagasse, modified with polyvinyl alcohol (PVA) and chitosan. The biofoam was synthesized using a baking process and evaluated for physical and mechanical properties, including water absorption, density, tensile strength, and biodegradability. To examine the effect of formulation, PVA concentrations ranged from 10% to 15%, while chitosan was added at 1.5%, 2.0%, and 2.5%. The result showed that water absorption values ranged from 6.4–14.2%, with densities at 0.370–0.613 g/cm³, tensile strengths 0.030–0.613 MPa, and biodegradability levels 74.4–100% within 14 days. Although the optimal formulation was achieved with 10% PVA and 2.5% chitosan, all samples met the Indonesian National Standard (SNI) for biodegradability, showing potential to replace conventional styrofoam.